Pemodelan Fatwa Ekonomi Syariah dan Karakteristiknya di Indonesia - Muhammad Hasanuddin; Mohd Solahuddin Bin Sharuddin; A. Jajang W. Mahri (Asy-Syari'ah, 2023)
Abtract: The DSN-MUI sharia economic fatwa has had a major influence in building the construction of sharia economic law in Indonesia. However, how the modeling of the fatwa was formed from 2000-2022 is still relatively rarely written about, as well as its characteristics. Therefore, this paper completes the empty space to be filled with authentic information regarding the Islamic economic fatwa modeling and its characteristics. That way, the empty space can be filled, and the discourse on sharia economic fatwa can continue to live and develop. In this paper, it is found that since 2000-2022 modeling the formation of Islamic economic fatwa in Indonesia has found two models, namely: the mustafti model and the initiation model. In the context of mustafti modeling, sharia economic fatwas were formed due to encouragement from mustafti from industry players, business people, health practitioners, professional institutions, associations, and regulators who asked DSN-MUI directly. Meanwhile, the initiation model is a model for forming a fatwa based on initiation among the internal DSN-MUI itself. As for its characteristics, the DSN-MUI fatwa is proactive and responsive. It is called proactive because the fatwa was produced from the DSN-MUI initiative. While it is called responsive because the DSN-MUI responds to each mustafti's questions by issuing a fatwa as the answer.